Chest Pain in the Patient with Arteria Lusoria: A Case Report - E. V. Reznik; Yu. V. Kemez (Архивъ внутренней медицины, 2021)
The most common anomaly of the aortic arch and its branches is the aberrant right subclavian artery – arteria lusoria. Usually, it produces dysphagia or dyspnea and chronic coughing.Our purpose is to underline that it is necessary to exclude the anomalies of the branches of the thoracic aorta, including arteria lusoria, in the patients with cardialgia of unknown origin.Clinical case. An 18-year-old female patient without a previously diagnosed chronic pathology was admitted to a hospital with chest pain after emotional stress for about an hour. The ECG revealed a sinus rhythm with a heart rate of 50 per minute, the normal direction of the electrical axis of the heart, the incomplete right bundle branch block, the negative T wave in the lead III. After excluding ischemic heart disease, acute coronary syndrome, pulmonary embolism, contrast-enhanced chest computed tomography revealed an aortic arch anomaly – a. lusoria.Conclusion. A. lusoria may manifest by cardiac pain. In patients with chest pain of unknown origin, it is advisable to include anomalies of the aorta and its branches, including the presence of the lusoria artery, in the range of differential diagnostics.